A modified basin type solar still: Experimental performance and economic study. (15th December 2015) - Ibrahim, Ayman G.M.; Allam, Elsayed E.; Elshamarka, Salman E.
Abstract: A solar desalination system working at sub-atmospheric pressure is investigated. The decrease of the saline water evaporation pressure allows a much reduction of energy required to operate the system. The desalination system consists of a solar basin connected to an external air-cooled condenser and utilizes a vacuum pump to develop the vacuum condition. The experimental results for different seasons are presented. A maximum desalination system efficiency of 40% is obtained. An enhancement of 16.2% and 29.7% in productivity and thermal efficiency, respectively are obtained compared with the conventional solar still. Eventually, a cost analysis is carried out to evaluate the constructed desalination system economically. Based on the analysis of the obtained results, the recommendations for improvement of the constructed system are outlined. Highlights: A modified basin type solar still is investigated experimentally. Vacuum condition and addition of separate air-cooled condenser are employed. Higher productivity and efficiency are obtained compared with conventional one. Comparable productivity cost per liter. Increasing cover transmissivity and recovery of heat of condensation are recommended.